Pengaruh Konten Media Sosial Terhadap Sikap Peduli Lingkungan Siswa Sekolah Dasar - Julio Purna Putra; Supriyadi; Amrina Izzatika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the effect of social media content on environmental awareness among elementary school students and the role of social media in supporting environmental education. The research employs a literature review with a qualitative approach, relying on data from various sources. The findings indicate that social media content focusing on environmental issues has the potential to enhance students' environmental awareness. Additionally, the active role of teachers and parents in guiding social media usage is crucial to ensure students access content that supports environmental education.